Exploring the Association between Diagnostic and Therapeutic Radiation and the Incidence of Vestibular Schwannoma: A Case–Control Study - Tessler, Idit; Chetrit, Angela; Gecel, Nir A.; Twig, Gilad; Perry, Avital; Wolfovitz, Amit (Journal of Neurological Surgery Reports, 2025)
Ionizing radiation is a known risk factor for various neoplasms, yet its link with vestibular schwannoma (VS) remains unclear. Given that VSs are benign tumors of the eighth cranial nerve, elucidating potential associations with radiation is of clinical interest. This study investigated the association between diagnostic and therapeutic head and neck radiation exposure and VS.In a case–control design, we enrolled 137 patients with VS, matched by age and sex with 659 controls. Data were obtained through structured interviews, capturing sociodemographic factors and history of therapeutic head and neck radiation, as well as imaging examinations (X-ray, computed tomography [CT], and magnetic resonance [MR], excluding the last 2 years). Weighted distributions were used to account for up to six controls per case. We used conditional logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs).The mean age of participants was 53 ± 14.6 years, with 50.4% females. An initial significant association was observed between therapeutic radiation and VS (adjusted OR = 4.94, 95% CI: 2.49–7.98). However, excluding participants who recently underwent radiation therapy attenuated this association (adjusted OR = 2.32, 95% CI: 0.59–9.07; p = 0.22). No significant associations were found for diagnostic imaging (ORs of 1.04 [0.86–1.25], 1.18 [0.73–1.92], and 1.19 [0.57–2.49] for X-ray, CT, and MR, respectively).Our findings do not support a significant relationship between either therapeutic or diagnostic head and neck radiation exposure and the risk of VS, once recent treatments are excluded. Additional large-scale studies are necessary to confirm these observations and to examine potential dose–response effects.
Keywords: vestibular schwannoma; diagnostic radiation; therapeutic radiation; case–control study; ionizing radiation